Nutrition and Schools Knowledge Summary - Laitsch, Daniel (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2009)
AbstractThis review examined 117 research articles using a policy framework generated in previous research. Findings include: students are experiencing both food insecurity and an “epidemic of obesity”; policymakers remain focused on achievement; provinces address nutrition in isolation; poverty is a significant contributor; restriction of food is not an effective treatment; nurses and training may strengthen health literacy; costs offer barriers to implementation and sustainability; teacher training, funding, nutritious foods, and health professionals are important; the impact of “one-off” programs is small; and there is limited implementation and evaluation of comprehensive approaches to school health.